Environmental sustainability with the role of green innovation and economic growth in India with bootstrap ARDL approach - Pachiyappan, Duraisamy; Alam, Md Shabbir; Khan, Uzma; Khan, Aarif Mohammed; Mohammed, Shariq; Alagirisamy, Kuppusamy; Manigandan, Palanisamy (Frontiers in Environmental Science, 2022)
This paper applies a novel Bootstrap Autoregressive Distributed Lag (BARDL) approach to investigate the relationship between green innovation (GI), economic growth (GDP), drama and film (D&F) industry, and environmental sustainability in India for the 1995 to 2020 period. The data has been checked for its stationarity by applying the Zivot and Andrews (ZA) unit root test, and the cointegration test results suggest a long-run equilibrium relationship between the variables. The empirical finding of long-run estimates reveals that 1% augments of GI, GDP, and D&F industry increase CO2 emissions by −0.079, 0.566%, and 0.143%, respectively. Furthermore, the main results indicate that GDP and the D&F industry have statistically significant positive effects on CO2 emissions, and GI has statistically significant negative effects on CO2 emissions. The GI leads to lower environmental damage by reducing carbon emissions. Regarding causal relationships, bidirectional causality is found between D&F and CO2 emissions, GI and CO2 emissions. In addition, a unidirectional causality is also revealed from GDP to CO2 emissions. Based on the finding of this study, policy implications are suggested for India.